2016
DOI: 10.1159/000445544
|View full text |Cite
|
Sign up to set email alerts
|

Trachyonychia and Twenty-Nail Dystrophy: A Comprehensive Review and Discussion of Diagnostic Accuracy

Abstract: Background/Aims: The term trachyonychia, also known as twenty-nail dystrophy, is used to describe thin, brittle nails with excessive longitudinal ridging. The term twenty-nail dystrophy has been incorrectly applied to other conditions that can affect all twenty nails. Therefore, we have conducted a comprehensive review of the clinical features of trachyonychia and have included a discussion regarding the diagnostic accuracy of this condition in the literature. Methods: In November and December 2015, we conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 49 publications
5
34
0
Order By: Relevance
“…Trachyonychia, which is a diagnosis made clinically, was mainly observed in the [6 to <12 years old] age group. Biopsies for diagnostic purposes are not recommended because whatever the diagnosis, trachyonychia does not lead to nail destruction . Annual follow‐up is usually suggested to reassure parents and their child.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Trachyonychia, which is a diagnosis made clinically, was mainly observed in the [6 to <12 years old] age group. Biopsies for diagnostic purposes are not recommended because whatever the diagnosis, trachyonychia does not lead to nail destruction . Annual follow‐up is usually suggested to reassure parents and their child.…”
Section: Discussionsupporting
confidence: 91%
“…Annual follow‐up is usually suggested to reassure parents and their child. Our study found improvement or cure in 75% of cases, confirming the good prognosis previously published, regardless of treatment . Park et al .…”
Section: Discussionsupporting
confidence: 91%
“…This condition was first described by Alkiewicz in 1950 while Hazelrigg et al . in 1977 observed a subtype of trachyonychia, which they called twenty‐nail dystrophy, where all twenty nails and toenails were uniformly affected; however, it is important to underline that trachyonychia can involve any number of nails and the term twenty‐nail dystrophy is quite aspecific because there are multiple conditions which can affect all twenty nails, aside from trachyonychia.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor , The diagnosis of trachyonychia is often challenging, and misdiagnoses, particularly as onychomycosis, are common . The correct diagnosis of trachyonychia is crucial because treatment options for trachyonychia include observation or active nonintervention, topical and systemic steroids, or immunomodulating agents, while onychomycosis should be treated with antifungal agents . Onychoscopy (nail dermoscopy) is a useful tool for various nail disorders .…”
mentioning
confidence: 99%